Factors Influencing the Formulation of A Viable Urban Development Policy in South Africa - Makhanye, Samu; Myrick, Darrell (Mediterranean Journal of Social Sciences, 2012)
At the time of the 1994 democratic elections, South African cities were characterised bysub-standard housing, service delivery backlogs and serious problems in municipalspending. Indeed, there were, and still are, spatial anomalies associated with â€œapartheidcitiesâ€ and the struggle to dismantle local government structures reminiscent of apartheidadministrations. High unemployment and poverty-stricken households further exacerbatedthe urban policy landscape. Nevertheless, the way forward was directed by the ANCâ€™sReconstruction and Development Programme (RDP) that aimed to address basic humanneeds. That same development programme provided the backdrop for a South AfricanConstitution (1996) that proclaimed inalienable rights for all South Africans â€“ housingbeing one of those paramount rights. Sadly, urban policies for human settlements werehastily developed and driven by political agendas that focused too far into the future,failing to address immediate housing needs. Moreover, urban policies were at timessimplistic and at times too complex, serving only to make policy formulation much moredifficult. This article discusses policy for urban development in the context of the politicaleconomy of South Africa. The aim is to explore the challenges and barriers to formulatingan urban policy.